A genome-wide combinatorial strategy dissects complex genetic architecture of seed coat colour in chickpea - Bajaj, Deepak; Das, Shouvik; Upadhyaya, Hari Deo; Ranjan, Rajeev; BADONI, SAURABH; Kumar, Vinod; Tripathi, Shailesh; Gowda, CL L.; Sharma, Shivali; Singh, Sube; Tyagi, Akhilesh; PARIDA, SWARUP K. (Frontiers in Plant Science, 2015)
The study identified 9045 high-quality SNPs employing both genome-wide GBS- and candidate gene-based SNP genotyping assays in 172, including 93 cultivated (desi and kabuli) and 79 wild chickpea accessions. The GWAS in a structured population of 93 sequenced accessions detected 15 major genomic loci exhibiting significant association with seed coat colour. Five seed colour-associated major genomic loci underlying robust QTLs mapped on a high-density intra-specific genetic linkage map were validated by QTL mapping. The integration of association and QTL mapping with gene haplotype-specific LD mapping and transcript profiling identified novel allelic variants (non-synonymous SNPs) and haplotypes in a MATE secondary transporter gene regulating light/yellow brown and beige seed coat colour differentiation in chickpea. The down-regulation and decreased transcript expression of beige seed coat colour-associated MATE gene haplotype was correlated with reduced proanthocyanidins accumulation in the mature seed coats of beige than light/yellow brown seed coloured desi and kabuli accessions for their coloration/pigmentation. This seed colour-regulating MATE gene revealed strong purifying selection pressure primarily in LB/YB seed coloured desi and wild Cicer reticulatum accessions compared with the BE seed coloured kabuli accessions. The functionally relevant molecular tags identified have potential to decipher the complex transcriptional regulatory gene function of seed coat coloration and for understanding the selective sweep-based seed colour trait evolutionary pattern in cultivated and wild accessions during chickpea domestication. The genome-wide integrated approach employed will expedite marker-assisted genetic enhancement for developing cultivars with desirable seed coat colour types in chickpea.